PENGARUH PENGGUNAAN ALAT PELINDUNG MATA TERHADAP KETAJAMAN PENGLIHATAN PEKERJA LAS DI KECAMATAN MANDAU, BENGKALIS RIAU - Widia Astin; Aras Mulyadi; Suyanto Suyanto (Jurnal Ilmu Lingkungan, 2016)
One negative impact for electric welders in the form of exposure radiation generated in the welding process that will result in visual acuity disturbances welders.This study was an observational study with cross sectional design is examined at the same independent variables, dependent variables and independent variables at the same time. The purpose of this study to know the effect of time on radiation for electric welders, types of eye protection used, consistency (compliance worker) in the use of eye protection equipment, working time and the influence of age on visual acuity in welding workers in in Kecamatan Mandau Kabupaten Bengkalis Riau with a total sample of 32 electric welders.Collecting data to see the sharpness of vision(visual acuity) was performed using a Snellen Optotype and questionnaires. The results showed that disturb ances in visual acuity (vision) in welders influenced by the time display (p-value = 0.001) and the consistency of the use of eye protection equipment by workers when performing welding (p-value = 0.001). There is no relationship or influence the type of eye protection equipment (p-value = 0.437) were used, age (p-value = 0.142) and working time (p-value = 0.669) on the occurrence of disturb ances in visual acuity welders in Kecamatan Mandau Kabupaten Bengkalis Riau. Owners of business are expected have high commitment to implementation of occupational health and safety regulation, follow the rule of Indonesian Labour Department in the application of working hours, minimize the radiation for welder and provide training about welding standards.